Lesbian potentiality and feminist media in the 1970s - Samer, Rox (Duke University Press, 2022)
In Lesbian Potentiality and Feminist Media in the 1970s, Rox Samer explores how 1970s feminists took up the figure of the lesbian in broad attempts to reimagine gender and sexuality. Samer turns to feminist film, video, and science fiction literature, offering a historiographical concept called “lesbian potentiality”—a way of thinking beyond what the lesbian was, in favor of how the lesbian signified what could have come to be. Samer shows how the labor of feminist media workers and fans put lesbian potentiality into movement. They see lesbian potentiality in feminist prison documentaries that theorize the prison industrial complex’s racialized and gendered violence and give image to Black feminist love politics and freedom dreaming. Lesbian potentiality also circulates through the alternative spaces created by feminist science fiction and fantasy fanzines like The Witch and the Chameleon and Janus. It was here that author James Tiptree, Jr./Alice B. Sheldon felt free to do gender differently and inspired many others to do so in turn. Throughout, Samer embraces the perpetual reimagination of “lesbian” and the lesbian’s former futures for the sake of continued, radical world-building.
Keywords: 1900-1999; 1970-1979; approches et analyses; arts; cinéma; communication; discipline; histoire et politique; lesbianisme; personnes lesbiennes; périodes historiques; ressource en ligne; thématiques; études littéraires

Visual Pleasure and Narrative Cinema - Mulvey, Laura (Screen, 1975)
Cet article se propose d'utiliser la psychanalyse pour découvrir où et comment la fascination du film est renforcée par des schémas de fascination préexistants déjà à l'œuvre au sein du sujet individuel et des formations sociales qui l'ont façonné. Il prend pour point de départ la façon dont le cinéma reflète, révèle et même joue sur la lecture droite et socialement établie de la différence sexuelle qui commande les images, les regards érotiques et le spectacle. Il est utile de comprendre ce qu'a été le cinéma, comment sa magie a opéré dans le passé, tout en tentant une théorie et une pratique qui remettront en cause ce cinéma du passé. La théorie psychanalytique est ainsi appropriée ici comme une arme politique, démontrant la manière dont l'inconscient de la société patriarcale a structuré la forme cinématographique.
Keywords: 1900-1999; 1970-1979; amériques; approches et analyses; cinéma; cours; discipline; fem1000; fem3200; male gaze; premier cycle; privilèges; psychanalyse; périodes historiques; ressource en ligne; régions géographiques; sciences; sciences humaines; sofia; systèmes d'oppressions; états-unis